2016
DOI: 10.1007/s13197-016-2229-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cooking methods on structure and quality of industrially frozen carrots

Abstract: The effect of boiling, steaming and microwaving on microstructure, texture and colour of raw and industrially frozen carrots was investigated. The raw carrots, after cooking, showed dehydrated and separated cells with swollen walls. The carrots subjected to blanching, freezing and followed by frozen storage exhibited marked tissue damages indicating deep oriented fissures. Cooking caused cellular dehydration and separation in the tissue, with the same intensity between raw and frozen carrots and independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…The reduction of b *, in comparison to the raw sample, was more visible for the longer cooking times. The decrease of L * indicates darkening, while the reduction of both a* and b * indicates a general colour loss, as already reported for cooked carrots . These observations may be related to a decrease and/or isomerisation of α ‐ and β ‐carotene, the orange pigments of which the pumpkin is rich, as previously reported by other authors …”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The reduction of b *, in comparison to the raw sample, was more visible for the longer cooking times. The decrease of L * indicates darkening, while the reduction of both a* and b * indicates a general colour loss, as already reported for cooked carrots . These observations may be related to a decrease and/or isomerisation of α ‐ and β ‐carotene, the orange pigments of which the pumpkin is rich, as previously reported by other authors …”
Section: Resultssupporting
confidence: 82%
“…The cutting test revealed a significant decrease of the shearing force (F s ) in comparison to the raw samples for both vegetables under all the cooking conditions. The obtained results may be related to the tissue damages caused by heating, as already reported by several authors 5,7 who observed the softening of vegetables when subjected to different cooking techniques. Such damages were described as cell plasmolysis and cell separation and have been attributed to the breakage of chemical bonds between the pectic components of middle lamellae, and the hydrolysis of some other components of the cell wall (i.e.…”
Section: Texture and Colour Analysissupporting
confidence: 75%
See 3 more Smart Citations